Optimization of flexible substrate by gradient elastic modulus design for performance improvement of flexible electronic devices. (25th April 2018) - Xia, Minggang; Liang, Chunping; Hu, Ruixue; Cheng, Zhaofang; Liu, Shiru; Zhang, Shengli
Abstract: It is imperative and highly desirable to buffer the stress in flexible electronic devices. In this study, we designed and fabricated lamellate poly(dimethylsiloxane) (PDMS) samples with gradient elastic moduli, motivated by the protection of the pomelo pulp by its skin, followed by the measurements of their elastic moduli. We demonstrated that the electrical and fatigue performances of a Ag-nanowire thin film device on the PDMS substrate with a gradient elastic modulus are significantly better than those of a device on a substrate with a monolayer PDMS. This study provides a robust scheme to effectively protect flexible electronic devices.